2020
DOI: 10.1021/acs.langmuir.9b03318
|View full text |Cite
|
Sign up to set email alerts
|

Amplification of Salt-Induced Protein Diffusiophoresis by Varying Salt from Potassium to Sodium to Magnesium Chloride in Water

Abstract: Salt-induced diffusiophoresis is the migration of a macromolecule or a colloidal particle induced by a concentration gradient of salt in water. Here, the effect of salt type on salt-induced diffusiophoresis of the protein lysozyme at pH 4.5 and 25 °C was examined as a function of salt concentration for three chloride salts: NaCl, KCl, and MgCl 2 . Diffusiophoresis coefficients were calculated from experimental ternary diffusion coefficients on lysozyme−salt−water mixtures. In all cases, diffusiophoresis of thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(30 citation statements)
references
References 60 publications
0
23
0
1
Order By: Relevance
“…A microfluidic approach for diffusiophoresis of macromolecules is demonstrated by Palacci et al for DNA focusing, , and later more groups visualized and studied diffusiophoresis of lipid vesicles, DNA, proteins, and other macromolecules. ,,, , In the studies by Palacci et al, , under a concentration gradient of LiCl set up across the flow, colloidal particles and λ-DNA showed transient diffusiophoretic focusing. The measurements and calculations for the peak propagation indicated that fluorescent-tagged λ-DNA behaves similarly to the polystyrene particles (carboxylate-modified PS; d = 200 nm).…”
Section: Particles Used In Experimental Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…A microfluidic approach for diffusiophoresis of macromolecules is demonstrated by Palacci et al for DNA focusing, , and later more groups visualized and studied diffusiophoresis of lipid vesicles, DNA, proteins, and other macromolecules. ,,, , In the studies by Palacci et al, , under a concentration gradient of LiCl set up across the flow, colloidal particles and λ-DNA showed transient diffusiophoretic focusing. The measurements and calculations for the peak propagation indicated that fluorescent-tagged λ-DNA behaves similarly to the polystyrene particles (carboxylate-modified PS; d = 200 nm).…”
Section: Particles Used In Experimental Studiesmentioning
confidence: 99%
“…This specific setting is not yet reported, but there have been studies about diffusiophoresis of protein in the context of ternary diffusion system. In the studies led by Annunziata et al, , diffusiophoresis of lysozyme using salt gradients (NaCl, KCl, MgCl 2 ) was reported. The authors provided an estimation of the zeta potential and mentioned potential microfluidic application using MgCl 2 .…”
Section: Particles Used In Experimental Studiesmentioning
confidence: 99%
“…The direct molecular evidence of formation of Na + /K + -anion clusters detected by in situ liquid SIMS could ultimately help determine a basis for understanding prenucleation cluster dynamics and thus controlling the crystallization behavior of gibbsite in alkaline aluminate solutions. More broadly, the in situ liquid SIMS technique could be used to explore the ion-pairing ability of rare earth ions or organic molecules such as peptides and proteins with different ionic liquids or additives that may facilitate the advancement of separation approaches to purify the rare earth elements or pharmaceuticals. , , Moreover, understanding ion-pair formation between organic ligands and metal ions, alkaline ions and organic species, Pb­(II) and halide ions, and charged electrolyte species and counterions in flow batteries may provide insights into the development of novel metal–organic frameworks (MOFs), perovskites, battery materials for energy storage, environment, and catalysis. …”
Section: Resultsmentioning
confidence: 99%
“…Understanding ion pairing of simple oppositely charged ions in electrolyte solutions and the effect of counterions on ion-pair formation is critical for material synthesis, catalysis, energy storage, environmental conservation, biological medicine, and so on. For example, formation of ion pairs can enhance the separation of organic molecules such as peptides and proteins from natural products and thus is a widely employed strategy in the preparation and analysis of pharmaceuticals. , Likewise, the desirable properties of phosphors can be promoted by optimizing the concentration of ion pairs between rare earth element dopants and counterions to improve the energy transfer . Moreover, crystal phases and their relative growth rates can be controlled by introducing different counterions to adjust the ion-pair formation behavior. ,,, …”
Section: Introductionmentioning
confidence: 99%
“…2,6 In some cases, the diffusiophoretic behaviour of proteins has been studied. 7 Surprisingly, a systematic study on the transport behaviour of DNA-like large anionic phosphatecontaining biopolymer over a gradient of ions has not been established to the best of our knowledge. In a few instances, electrophoresis, optothermal diffusiophoresis, or gel-based diffusiophoresis has been studied in the presence of salts to understand important features, such as DNA transport or focussing on nanopores, non-linear sensing-related analytical applications.…”
mentioning
confidence: 99%